Effect of different immobilization media on breakdown of whey proteins by Streptococcus thermophilus - YILMAZ GÖLER, AYŞE MİNE (My University, 2022)
Objective: In this study, we aimed to compare the efficiency of different immobilization media to facilitate breakdown of whey proteins by Streptococcus thermophilus (S. thermophilus). Materials and Methods: S. thermophilus was isolated from yoghurt. High-protein whey powder was present in fermentation media and two-phase dispersion technique was used for immobilization of S. thermophilus in agar, agarose and κ-carrageenan. Total protein after fermentation of whey proteins with S. thermophilus in different media was measured. We have also performed sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis to observe changes in individual whey proteins after fermentation in different media. Results:Total protein concentration showed a significant decrease at the end of 24 hours of fermentation in all media. SDS-PAGE results showed that the amount of both α-lactalbumin and β-lactoglobulin were reduced in all immobilization media compared to control. The effect of κ-carrageenan was considerably higher compared to other media. Conclusion:Our results showed that immobilization in κ-carrageenan increased the breakdown of whey proteins by S. thermophilus and can be used to increase fermentation efficiency
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Mikrobiyoloji ve Klinik Mikrobiyoloji; Diğer; Medicine; Health Sciences; Fundamental Medical Sciences; Biochemistry; Microbiology and Clinical Microbiology; Other; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; Mikrobiyoloji; TIP, GENEL & DAHİLİ; MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MICROBIOLOGY; MEDICINE, GENERAL & INTERNAL; İmmünoloji ve Mikrobiyoloji (çeşitli); Aile Sağlığı; Mikrobiyoloji (tıbbi); Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Biyokimya (tıbbi); Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; Immunology and Microbiology (miscellaneous); Microbiology; Family Practice; Microbiology (medical); Fundamentals and Skills; General Health Professions; Pathophysiology; Biochemistry (medical); Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Life Sciences; alpha-lactalbumin; beta-lactoglobulin; Fermentation; Immobilization; kappa-carrageenan; LACTIC-ACID; LACTOBACILLUS-BULGARICUS; CELLS; CARRAGEENAN; CASEI; α-lactalbumin; β-lactoglobulin; Fermentation; Immobilization; κ-carrageenan